2019
DOI: 10.3390/infrastructures5010002
|View full text |Cite
|
Sign up to set email alerts
|

Model Calibration Methodology to Assess the Actual Lighting Conditions of a Road Infrastructure

Abstract: Street lighting plays an important role in the comfort and safety of drivers and pedestrians, so the control and management of the lighting systems operation and consumption is an essential service for a city. In this document, a methodology is presented to calibrate lighting models in order to assess the lighting performance through simulation techniques. The objective of this calibration is to identify the maintenance factor of the street lamps, determine the real average luminance coefficient of the road pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The r -tables can also be seen as BRDFs reduced at two dimensions. A few studies were interested in r -table modelling 27,32,33 but many dealt with BRDF models. 46 Suitable analytic BRDF models are not often available and a common solution is to choose a suitable function space to approximate measured BRDFs in that space.…”
Section: R-tables Basis Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The r -tables can also be seen as BRDFs reduced at two dimensions. A few studies were interested in r -table modelling 27,32,33 but many dealt with BRDF models. 46 Suitable analytic BRDF models are not often available and a common solution is to choose a suitable function space to approximate measured BRDFs in that space.…”
Section: R-tables Basis Functionsmentioning
confidence: 99%
“…[20][21][22][23][25][26][27] Thanks to recent imaging luminance measurement devices (ILMD) 26,[28][29][30][31] and lighting software, 3,4 it is also possible to compare simulated versus measured photometric parameters and luminance maps with a feedback loop to aim for the right model. 32,33 An original method has also been carried out by Buschmann et al 34 using a dedicated on-site illumination set-up. Thanks to a calibrated luminaire and luminance image processing, some r-table elements are calculated, and used to simulate luminance maps.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that using the real photometric characteristics of the road surface can improve the quality of lighting, reduce energy costs, and limit obtrusive light [17]. Thus, in recent years, there are more and more scientific works aimed at measuring or modelling the optical properties of pavements [18][19][20][21][22][23] to optimize light. Working groups federate coating manufacturers and lighting designers [24] to better size lighting installations at the design stage or during a renovation.…”
Section: Introductionmentioning
confidence: 99%
“…In a short time, it will be possible to misremember "the old metal box on four wheels" because the cars that will be driven shortly will be smarter and will allow performing actions unimaginable until recently [4]. The car will no longer be a mere means of transport because, thanks to new technologies, it will be able not only to simplify the driver's life but also to increase safety on the road [5][6][7].…”
Section: Introductionmentioning
confidence: 99%